Implementation Of Wadiah Agreements In Indonesian Hajj Savings Products At Bank Syariah Indonesia KCP Cinunuk - Santi Nur Rohmah Agustiani (Penerbit Hellow Pustaka, 2023)
The purpose of this research is to find out how the wadiah contract is implemented in Indonesian Hajj savings products at Bank Syariah Indonesia KCP Cinunuk. The method of this research uses descriptive qualitative methods. From the results of research that has been carried out, the wadiah contract that will be used in the Indonesian Hajj savings product at Bank Syariah Indonesia KCP Cinunuk is the wadiah yad adh-dhamanah contract. With the provisions, customers must reach the Hajj savings target of twenty-five million rupiah, if they do not reach this target then the customer cannot withdraw the money entrusted to the bank. As a deposit recipient, the money that the customer deposits with the bank can be managed by the bank and distributed back to the community in the form of a loan. From the results of the distribution of funds, profits obtained by the bank will be returned to the customer (the depositor) in the form of a bonus that has not been previously agreed upon.